The type specimens of Sarcophagidae (Diptera) housed at the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia” - Mulieri, Pablo R. (2010)
Fil: Mulieri, Pablo Ricardo. ANLIS Dr.C.G.Malbrán. Centro Nacional de Diagnóstico e Investigación en Endemo-Epidemias; Argentina.